Inverse Electromagnetic Scattering Models for Sea Ice - Golden, K. M.; Borup, D.; Cheney, M.; Cherkaeva, E.; Dawson, M. S.; Ding, K. H.; Fung, A. K.; Isaacson, D.; Johnson, S. A.; Jordan, A. K.; Kong, J. A.; Kwok, R.; et al. (2004)
Inverse scattering algorithms for reconstructing the physical properties of sea ice from scattered electromagnetic field data are developed.